Matilda - Dahl, Roald; Escott, john (Harlow, Essex : Pearson Education, 2008)
Matilda applies her untapped mental powers to rid the school of the evil, child-hating headmistress, Miss Trunchbull, and restore her nice teacher, Miss Honey, to financial security.
5.2
3-6.
3-6
Keywords: Humorous stories; Schools -- Fiction; Humorous fiction; School stories